2010
DOI: 10.1063/1.3380848
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure phase transitions and compressibility of wolframite-type tungstates

Abstract: This paper reports an investigation on the phase diagram and compressibility of wolframite-type tungstates by means of x-ray powder diffraction and absorption in a diamondanvil cell and ab initio calculations. The diffraction experiments show that monoclinic wolframite-type MgWO 4 suffers at least two phase transitions, the first one being to a triclinic polymorph with a structure similar to that of CuWO 4 and FeMoO 4 -II. The onset of each transition is detected at 17.1 and 31 GPa. In ZnWO 4 the onset of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
63
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 42 publications
21
63
1
2
Order By: Relevance
“…Our findings for NiWO 4 suggest that 13% HF admixture gives the best result for both lattice dynamics and the equilibrium structure. [47] for simple LDA-type Hamiltonian [48]. On the contrary, our previous calculations [19] using hybrid PBE0 Hamiltonian [27] with 25% HF admixture overestimated the frequencies of the stretching WO modes by ∼ 34 cm −1 in ZnWO 4 and ∼ 39 cm…”
Section: Resultsmentioning
confidence: 78%
“…Our findings for NiWO 4 suggest that 13% HF admixture gives the best result for both lattice dynamics and the equilibrium structure. [47] for simple LDA-type Hamiltonian [48]. On the contrary, our previous calculations [19] using hybrid PBE0 Hamiltonian [27] with 25% HF admixture overestimated the frequencies of the stretching WO modes by ∼ 34 cm −1 in ZnWO 4 and ∼ 39 cm…”
Section: Resultsmentioning
confidence: 78%
“…8,9 This particular transformation induced by non-hydrostatic conditions has been observed experimentally in wolframites ZnWO 4 and MgWO 4 at around 17 GPa (Ref. 8) and more recently at a similar pressure in MnWO 4 by Dai et al 10 In quasi-hydrostatic conditions, the absence of deviatory stresses has proved to allow these materials to retain the monoclinic wolframite structure up to pressures around 26 GPa (Refs. 5 and 9) with a predicted doubled unit-cell and a symmetry increase for the HP phase that remains unsolved experimentally.…”
Section: Introductionmentioning
confidence: 98%
“…7 A theoretical work has shown that the monoclinic (P2/c) wolframite structure is energetically competitive with a triclinic (P 1) one of CuWO 4 -type. 8 On the other hand, experiments have demonstrated that non-uniform stress due to non-hydrostatic components can favor a structural transformation from the monoclinic to the triclinic structure. 8,9 This particular transformation induced by non-hydrostatic conditions has been observed experimentally in wolframites ZnWO 4 and MgWO 4 at around 17 GPa (Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These unit cells were modeled through the Visualization for Electronic and Structural Analysis (VESTA) software version 3.1.1 for Windows 41 using lattice parameters and atomic positions obtained from Rietveld refinement data shown in Table 1. FeWO 4 crystals belong to a wolframite-type monoclinic structure with a space group of (P2/c), a point-group symmetry (C 4 2h ) and two formulae per unit cell (Z = 2) 42 Fig. 3(a-c) verifies that bonds between O-Fe-O and O-W-O atoms were projected out of unit Fig.…”
Section: Characterizationsmentioning
confidence: 99%